Code Switching in English Language Learning at Pabelan Islamic Boarding School - Cintia Yudita (RETORIKA: Jurnal Ilmu Bahasa, 2019)
This research aims to describe the use of code switching in English language learning, in terms of the form of code switching, the kind of code switching, the aim of code switching, the function of code switching and the causal factors of code switching. This study belongs to qualitative research. The subjects of this research were the English teacher and students. Meanwhile, the data were utterances of English teacher and students that contained code switching. The data were collected through observation, recording, note-taking and interview. Classroom activities, particularly in the teaching of English language, were recorded on video tapes and field notes. The data analysis revealed several findings. First, both teacher and students used word form of code switching, phrase form of code switching and sentence form of code switching when they were in the classroom. Second, the English teacher and the student used intern and extern code switching, temporary code switching, situational and metaphorical code switching. Third, the aim of using code switching done by the teacher and students were compensating for language limitation, to explain the material and strategy in teaching learning process. Fourth, the functions of code switching for teachers and student were as clarification, emphasis, repetition, translation, checking for understanding, tool for communication, developing vocabulary and tolerance. Fifth, the factors that caused code switching were to fulfil a need, to express or declare solidarity, to respect the listener and to be more informative.